HUBUNGAN PENGETAHUAN IBU DENGAN KEBERHASILAN PEMBERIAN ASI EKSLUSIF - Destria Efliani; Ika Permanasari; Nurhayati (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Exclusive breastfeeding can reduce child mortality globally by 10% every year. Exclusive breastfeeding promotion is an effective intervention effort to reduce mortality. lack of knowledgeone the factors that influence of succes of exlusive breatfeeding. The purpose of this research is to know the relationship of maternal knowledge with the success of exclusive breastfeeding in the Working Area of Puskesmas Umban sari Rumbai District, Pekanbaru City. This type of research uses Quantitative with cross sectional design, with a population of 70 mothers who have babies aged 6-12 months and a sample of 60 respondents. Accidental sampling techniques with research instruments use questionnaires, and statistical tests using chi square test. The results of the study were obtained, mothers with less knowledge 14 respondents (23.3%), enough knowledge 20 respondents (33.3%), and good knowledge 26 respondents (43.3%), the success of exclusive breastfeeding 33 infants (55.0%), as well as the unsuccessful exclusive breastfeeding 27 (45.0%). Chi Square test results showed signification p= 0.002 ≤ α (0.05), meaning H1 was accepted, so there is a relationship between knowledge and the success of exclusive breastfeeding. It is expected to increase health education activities by Counseling to the community